Mapping breast and prostate cancer in the Brazilian public health system: study protocol of the Onco-Genomas Brasil - Schuch, Jaqueline Bohrer; Bordignon, Cláudia; Rosa, Mahira Lopes; de Baumont, Angélica Cerveira; Bessel, Marina; Macedo, Gabriel S.; Rosa, Daniela Dornelles (Frontiers in Oncology, 2024)
Background: Breast and prostate cancers are the most common malignancies diagnosed in women and men respectively, and present with great clinical heterogeneity, even in tumors with the same histology and same site of origin. Somatic and germline molecular alterations in DNA may have prognostic and predictive impact, influencing response to therapies and overall survival. Our aim is to characterize the somatic and germline genomic landscape of women with locally advanced HER2-positive breast cancer and men with metastatic prostate cancer in Brazil. Secondarily, we aim to identify genetic variants associated with tumor prognosis and treatment response, identify patients carrying pathogenic alterations in cancer-predisposing genes, and characterize the genetic ancestry of the population included in the study.Methods: This observational multicenter cohort study will include 550 adult patients from the five macro-regions of Brazil, divided into two arms: 1) breast cancer and 2) prostate cancer. Clinical and pathological data will be collected, as well as DNA samples from peripheral blood and tumor samples. In arm 1, the inclusion criteria are a histological diagnosis of breast carcinoma with overexpression of HER-2, clinical stage II or III, and current neoadjuvant treatment with chemotherapy plus trastuzumab. In arm 2, the criterion is a histological diagnosis of prostate adenocarcinoma, clinical stage IV. Whole-exome sequencing (WES) will be performed to identify variants that may be drivers and/or actionable in a specific patient or tumor. These variants will be interpreted and classified according to their population frequencies, in silico predictors, functional studies, and literature data, following international guidelines proposed by expert societies.Discussion: This trial will contribute to the construction of a robust database that should provide a better understanding of the genomic profile of patients with breast and prostate cancer in Brazil.Considering the miscegenation of the Brazilian population, knowledge generated from these data will have implications for future studies of this specific population.